Agaporomorphus sharynae, a new species of diving beetle (Coleoptera: Dytiscidae: Copelatinae) from Venezuela - Miller, Kelly B. (Zootaxa, 2014)
Agaporomorphus sharynae sp. n. is described from Amazonas, Venezuela. Agaporomorphus Zimmermann, 1921 now includes nine known species. The new species is part of the A. knishi species group since it has similarly convoluted male genitalia with rows of setae on the dorsal surface. Males can be separated from those of other members of the genus by the structure of the abdominal ventrites, shape of the antennae, and shape of the male median lobe. The cladistic analysis of K.B. Miller & Wheeler (2008) is modified to include the new species. The habitus and male and female genitalia are illustrated, and male genitalia of other species of the A. knishi species group are illustrated for comparison.